Designing Oral Health Curriculum That Facilitates Greater Integration of Oral Health Into Overall Health - Mays, Keith A. (Frontiers in Dental Medicine, 2021)
For several decades, health professions education has been transforming; pedagogical constructs such as active learning, recorded lectures, electronic assessment, asynchronous content delivery, and interprofessional education and practice. However, the typical oral health curriculum has need for further transformation to ensure graduates' ability to function in an integrated health system. There is significant literature outlining associations between oral health and overall health, therefore, it is paramount that oral health learners develop skills to collaborate in an integrated model. Satcher, in 2000, outlined the gravity of oral health inequities and the importance of oral health. He said, “Too little time is devoted to oral health and disease topics in the education of non-dental health professional.” However, on the contrary typical oral health curriculum provide knowledge acquisition of topics related to overall health but isn't specifically designed to guide integrated care. In order to increase integrated care, groups like the Interprofessional Education Collaborative (IPEC) have developed competencies for interprofessional education and collaborative practice that guides the training of health professionals. One way to improve integration is accreditation standards that guide transformation as well incorporate IPEC competencies. Having competencies is important to prepare learners to function in clinics like Kaiser Permanente's medical-dental integration model that rely upon teams and teamwork and clarity of roles and responsibilities. This manuscript outlines principle of oral health curriculum that facilitate graduates ability to work in an integrated health system and how that contributes to the improvement overall health of patients.